A Sensitive THz Fingerprint Sensor Based on Silicon Cylindrical Trimers for the Detection of Kresoxim-methyl - Wanxin Nie; Mengya Pan; Yanpeng Shi; Wenbin Shu; Huanyu Li; Wenyao Yu; Shuo Liu; Yifei Zhang (Photonics)
THz waves have garnered significant attention across multiple domains, particularly in high-sensitivity sensing applications. Metamaterials are applicable in THz sensors owing to their exceptional sensitivity, particularly in refractive index measurement and pesticide identification. This paper proposes a THz metamaterial sensor for detecting ether kresoxim-methyl. The sensor comprises a periodic array of silicon cylindrical trimers organized on a silicon substrate. Resonances in the guided mode, dictated by bound states in the continuum spectrum, can be stimulated by meticulously configuring the geometric arrangement of the silicon column trimer. The sensor demonstrates a Q-value of up to 143 at the resonant frequency. The detection of pesticide residues achieved high sensitivity and specificity, with a detection limit of 37.74 μg/cm2. This study presents a novel alternative for THz metamaterial sensors characterized by high sensitivity and a broad spectrum of pesticide concentration detection. The sensor platform developed in this paper, utilizing conventional CMOS technology, is posited as a potential detection instrument for herbicide and pesticide residues in agriculture and food.